1991
DOI: 10.1002/app.1991.070420113
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between chemical and physical networks in crosslinked and plasticized PVC

Abstract: SYNOPSISThe effect of crosslinking of plasticized PVC on the mechanical properties has been investigated. Crosslinking was performed by using a dithioltriazine, and penetration as a function of temperature was used to follow the changes in mechanical properties. Changes in the melting behavior were detected by differential scanning calorimetry. Even rather low levels of gel content gave a substantial reduction in penetration in the interval 60-llO"C, while a more complete reaction prevented major penetration u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It can be seen that X c and T m change no more with the increase of gel fraction at the same annealing conditions. Hjertberg et al 19 observed the increase of T m for high crosslinked PVC and considered that chemical crosslinking would decrease the mobility of PVC chains. However, the conclusion from Table II seems to be that the effect of chemical crosslinking on the recrystallization process could be ignored for lightly crosslinked PVC-TPE.…”
Section: Recrystallization Behavior Of Chemical Crosslinked Pvc-tpementioning
confidence: 99%
“…It can be seen that X c and T m change no more with the increase of gel fraction at the same annealing conditions. Hjertberg et al 19 observed the increase of T m for high crosslinked PVC and considered that chemical crosslinking would decrease the mobility of PVC chains. However, the conclusion from Table II seems to be that the effect of chemical crosslinking on the recrystallization process could be ignored for lightly crosslinked PVC-TPE.…”
Section: Recrystallization Behavior Of Chemical Crosslinked Pvc-tpementioning
confidence: 99%
“…Above T g , softening depends on the melting of these crystallites, but can be modified by a chemical crosslinked network. 22 The temperature at which high temperature softening was detectable was increased for all samples containing peroxide to approximately 190°C. The optimum peroxide concentration for minimum softening was 0.5-1.0 phr, and appeared to decrease within this range as TMPTMA concentration increased.…”
Section: Thermomechanical Analysismentioning
confidence: 91%
“…It is interesting to note that the catalyst does not appear to have an important effect on crosslinking rate. The effect of increasing the 34 mentioned that diffusion of that the catalyst is vital to shorten the crosslinkwater from the external environment has practiing time. Narkis et al, 30 however, mentioned that cally no effect on the crosslinking.…”
Section: Degree Of Crosslinkingmentioning
confidence: 98%